2018
DOI: 10.5194/isprs-archives-xlii-2-407-2018
|View full text |Cite
|
Sign up to set email alerts
|

Determining Geometric Parameters of Agricultural Trees From Laser Scanning Data Obtained With Unmanned Aerial Vehicle

Abstract: The estimation of dendrometric parameters has become an important issue for agriculture planning and for the efficient management of orchards. Airborne Laser Scanning (ALS) data is widely used in forestry and many algorithms for automatic estimation of dendrometric parameters of individual forest trees were developed. Unfortunately, due to significant differences between forest and fruit trees, some contradictions exist against adopting the achievements of forestry science to agricultural studies indiscriminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, UAV-based optical data and derived point clouds and digital surface models are more likely to prove beneficial for top of canopy information extraction. Studies have shown that UAV-based LiDAR data with high point density (3200 points/m 2 ) can successfully provide crown identification (92% of trees) and highly accurate crown height estimates (RMSE = 0.09 m, R 2 = 0.96) for horticultural tree crops [79]. Therefore, UAV-based data may provide an alternative to ALS and TLS data for orchard scale (<1 km 2 ) canopy structure mapping of horticultural tree crops.…”
Section: Capacity Of Als and Tls Data For Imporved Orchard Managementmentioning
confidence: 99%
“…However, UAV-based optical data and derived point clouds and digital surface models are more likely to prove beneficial for top of canopy information extraction. Studies have shown that UAV-based LiDAR data with high point density (3200 points/m 2 ) can successfully provide crown identification (92% of trees) and highly accurate crown height estimates (RMSE = 0.09 m, R 2 = 0.96) for horticultural tree crops [79]. Therefore, UAV-based data may provide an alternative to ALS and TLS data for orchard scale (<1 km 2 ) canopy structure mapping of horticultural tree crops.…”
Section: Capacity Of Als and Tls Data For Imporved Orchard Managementmentioning
confidence: 99%
“…In this method, the simplex of the underlying triangulation is compared with the specified α, deleting the simplex with an empty external sphere and a square radius greater than the defined α. Then the volume of the 3D object is calculated [56]. It should be noted that when α is large enough, the canopy reconstruction effect will be similar to that of a CH algorithm.…”
Section: Vb Algorithmmentioning
confidence: 99%
“…Unoccupied aerial vehicles (UAVs) are another remote sensing platform suited for integration with miniaturized sensor systems that offer potential for accurate canopy structure mapping, including parameters such as crown area, tree height and crown volume for horticultural trees for farm scale applications (Torres-Sánchez et al, 2015, Jiménez-Brenes et al, 2017. Studies have shown that UAV based LiDAR data with high point density (3200 points/m 2 ) can successfully provide crown identification (92% of trees) and highly accurate canopy height estimates (RMSE = 0.09 m, R 2 = 0.96) for horticultural tree crops (Hadas et al, 2018). Therefore, UAV based data may provide an alternative to ALS and TLS data for farm scale (< 1 km 2 ) canopy structure mapping of horticultural tree crops.…”
Section: Discussionmentioning
confidence: 99%